Analysis of Jambi University's Early Childhood and Primary Education Program for a Global Competitive Generation - Yantoro Yantoro; Destrinelli Destrinelli; Hendra Sofyan; Bunga Ayu Wulandari; Issaura Sherly Pamela; Uswatul Hasni; Rizki Surya Amanda (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article analyses educational programs for preparing a generation with global competitiveness in the Department of Early Childhood and Elementary Education, Jambi University using a qualitative approach and critical analysis. Furthermore, the data collection techniques used include interviews, observation, and documentation. The data analysis technique is the Miles and Huberman model, including reduction, presentation, and verification. The results showed that there are several programs to prepare a generation of global competitiveness, including 1) Organizing training and workshops to prepare a generation with global competitiveness, 2) Reframing for Global Competitiveness, 3) Organizing Focus Group Discussions (FGD), 4) Implementation of Student Extracurricular Activities, 5) Socialization of Student Achievement Improvement.